Cambios y continuidades en la percepción y demandas indígenas sobre el territorio en la Amazonía peruana - Espinosa, Óscar (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
This article explores changes and continuities in political demandsconcerning territorial rights as they have been articulated byindigenous organizations of the Peruvian Amazon over recentdecades. Its main objective is to demonstrate how particular historicalconjunctures have influenced the ways in which these groups havefocused their efforts in defense of what they consider to be a crucialelement of their way of life, increasingly threatened by incursionsfrom modern society, capitalism and processes of globalization. Theanalysis rejects depictions of the indigenous peoples as passive, opento manipulation by outside interests. At the same time, it provides amore profound understanding of the changes that are taking placewithin indigenous societies with respect to their perception of, andrelationship to, their territories.

En el presente artículo exploramos los cambios y continuidades enlas reivindicaciones que sobre el territorio han planteado los pueblosindígenas de la Amazonía peruana a través de sus organizaciones enlas últimas décadas. El objetivo central reside en explicar cómo endistintas coyunturas estas sociedades han enfrentado la defensa de loque consideran una parte esencial de su forma de vida que se hallacada vez más amenazada frente al avance de la sociedad moderna,del capitalismo y de la globalización. Esta revisión nos permitirádesbaratar aquellos argumentos que califican a los indígenas comosujetos pasivos, manipulables y a merced de intereses ajenos; y almismo tiempo, nos permitirá comprender mejor los cambios que sevienen produciendo al interior de las sociedades indígenas en supercepción y en su relación con el territorio.
Changes and continuities in the Indigenous perceptions and politicaldemands about their territory: the case of the Indigenous Peoples ofthe Peruvian Amazon region
Keywords: Amazonía peruana; Pueblos indígenas; Organizaciones indígenas; Territorio; Derechos indígenas; Modernización; https://purl.org/pe-repo/ocde/ford#5.04.03